Characteristics of Market Communication in Modern Business - Lazarević-Moravčević, Marija; Domazet, Ivana; Lazić, Milena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The subject of this paper is the analysis of the role of internet marketing in the marketing communication strategy of modern organizations. The paper points out the role of modern information technology and its importance in market communication. By applying new technological solutions, communication with the market becomes effective and efficient, which contributes to the improvement of the competitive position of the company. This paper aims to identify the basic specifics of internet marketing, as well as to assess its involvement in overcoming the problems that have arisen in business and communication with the emergence of the coronary virus pandemic. The paper applied the desk-research method, where the sources of data were primarily papers and publications from scientific journals and other professional literature in the field of marketing, as well as official data, databases and reports of relevant institutions. In conclusion, the authors state that the classical approach to market communication due to numerous shortcomings is not an adequate solution for marketing-oriented organizations, especially in times of crisis. The combination and integration of modern and traditional marketing instruments stand out as the most effective solution. Pointing out the basic advantages that are achieved by applying modern forms of market communication, the paper could contribute to the improvement of the practice of market communication of business systems, especially in situations that can be presented as a crisis.